The Implications of Mandating Photovoltaics on all New Homes. (December 2015) - Berry, Stephen; Whaley, David
Abstract: The transition to near zero energy and near zero carbon homes places the policy focus firmly on the widespread application of renewable energy technologies by the mainstream building industry. This systemic change from typical business practices for house design and construction to embrace the application of photovoltaic technology is likely to come with significant risk to policy outcomes. Using evidence drawn from a reasonably large near zero energy housing estate in Australia, the use of building energy regulations to facilitate the application of photovoltaics may not deliver the expected policy outcome. Lessons learnt from Australia point to issues related to regulatory design, industry training, and compliance assessment. Addressing these issues will be essential to achieve low carbon policy intentions.